A historical glance at different schools: theoretical and methodological perspectives (the example of the «INOVAR» project) - Sousa Pintassilgo, Joaquim António (Historia y Memoria de la Educación, 2019)
The aim of this article is to present a set of theoretical and methodological reflections raised by the development of the project INOVAR — «Itineraries of pedagogical innovation: reference schools and experiences in Portugal in the twentieth century», which started in May 2016 and whose completion is scheduled for April 2019. This is a Research and Development project funded by the Portuguese Foundation for Science and Technology. Its purpose is to map a wide set of innovative, different or alternative schools and experiences that were developed in Portugal in the twentieth century, in particular in its second half; to produce monographic historical narratives on each of the schools and experiences; and to describe the pedagogical models they were inspired by, as well as the pedagogical projects that underpinned their activity. We hope to present in this article some aspects of the theoretical framework of INOVAR, as well as to analyse some of its key concepts. With the aim of drawing on concrete examples, we focus on one of the project’s research topics — that which addresses A Torre, a school created in 1970 and still in operation today.